Viability of musharakah as an alternative financing mode for small and medium enterprises: The cases of Klang Valley and Selangor, Malaysia - Abdul Razak, Dzuljastri; Mohammed, Mustafa Omar; Abdul Rahman, Nur Hasnida (2016)
Small and Medium Enterprises ("SMEs") have been recognized as one of the most important component that contributes towards the economic growth of many countries around the world. Despite its importance, SMEs have limited access to external financing that is dominated by debt financing. They have difficulty in fulfilling debt requirements particularly in providing collateral, coping with high interest/ profit payment and adapting to credit rationing. Such limitations curb their growth and expansion. Therefore, there is a need to explore an alternative financing, which is more accessible by SMEs. This study examines the viability of Musharakah as an alternative financing mode for SMEs.